The Utilization of Environment on Kambang Island as a Learning Resource on Social Studies: A Literature Study - Muhammad Rezky Noor Handy; Muhammad Adhitya Hidayat Putra; Siti Zulfah; Nor Azizah; Siti Nor Laila Savitri; Rusmaniah Rusmaniah (The Kalimantan Social Studies Journal, 2023)
Utilization of the environment as part of social studies learning is currently the main topic for delivering teaching material in class. Kambang Island is a form of environment which is a unique natural tourist area with its flora and fauna. Therefore, the purpose of writing this article is to describe Kambang Island as a Social Sciences Learning Resources. The research is a literature study by examining manuscripts and books about Kambang Island as a social studies learning resource, through the stages of data collection, conceptualization, analysis and drawing conclusions. Kambang Island has unique flora and fauna which are characteristic of the Barito River region, which is based on the theme of class VII social studies teaching materials, namely People, Places and Environment, especially with environmental-based social studies learning resources. Kambang Island illustrates or delivers information to students using various learning media, whether in the form of visuals or audio-visuals, are brought into the classroom during learning in accordance with the learning plan prepared by the teacher.